The Role of Universities in the Triple Helix model of innovation management within the biotechnology industry, Case example: Turku Science Park Network - Syväperä, Kristiina (My University, 2013)
Biotechnology has been recognized as the key strategic technology for industrial growth. The industry is heavily dependent on basic research. Finland continues to rank in the top 10 of Europe's most innovative countries in terms of tax-policy, education system, infrastructure and the number of patents issued. Regardless of the excellent statistical results, the output of this innovativeness is below acceptable. Research on the issues hindering the output creation has already been done and the identifiable weaknesses in the Finland's National Innovation system are the non-existent growth of entrepreneurship and the missing internationalization. Finland is proven to have all the enablers of the innovation policy tools, but is lacking the incentives and rewards to push the enablers, such as knowledge and human capital, forward. Science Parks are the biggest operator in research institutes in the Finnish Science and Technology system. They exist with the purpose of speeding up the commercialization process of biotechnology innovations which usually include technological uncertainty, technical inexperience, business inexperience and high technology cost. Innovation management only internally is a rather historic approach, current trend drives towards open innovation model with strong triple helix linkages. The evident problems in the innovation management within the biotechnology industry are examined through a case study approach including analysis of the semi-structured interviews which included biotechnology and business expertise from Turku School of Economics. The results from the interviews supported the theoretical implications as well as conclusions derived from the pilot survey, which focused on the companies inside Turku Science Park network. One major issue that the Finland's National innovation system is struggling with is the fact that it is technology driven, not business pulled. Another problem is the university evaluation scale which focuses more on number of graduates and short-term factors, when it should put more emphasis on the cooperation success in the long-term, such as the triple helix connections with interaction and knowledge distribution. The results of this thesis indicated that there is indeed requirement for some structural changes in the Finland's National innovation system and innovation policy in order to generate successful biotechnology companies and innovation output. There is lack of joint output and scales of success, lack of people with experience, lack of language skills, lack of business knowledge and lack of growth companies.